Gender differences in the neural network of facial mimicry of smiles – An rTMS study. (September 2015) - Korb, Sebastian; Malsert, Jennifer; Rochas, Vincent; Rihs, Tonia A.; Rieger, Sebastian W.; Schwab, Samir; Niedenthal, Paula M.; Grandjean, Didier
Abstract: Under theories of embodied emotion, exposure to a facial expression triggers facial mimicry. Facial feedback is then used to recognize and judge the perceived expression. However, the neural bases of facial mimicry and of the use of facial feedback remain poorly understood. Furthermore, gender differences in facial mimicry and emotion recognition suggest that different neural substrates might accompany the production of facial mimicry, and the processing of facial feedback, in men and women. Here, repetitive transcranial magnetic stimulation (rTMS) was applied to the right primary motor cortex (M1), the right primary somatosensory cortex (S1), or, in a control condition, the vertex (VTX). Facial mimicry of smiles and emotion judgments were recorded in response to video clips depicting changes from neutral or angry to happy facial expressions. While in females rTMS over M1 and S1 compared to VTX led to reduced mimicry and, in the case of M1, delayed detection of smiles, there was no effect of TMS condition for males. We conclude that in female participants M1 and S1 play a role in the mimicry and in the use of facial feedback for accurate processing of smiles.